Karakteristik Morfologi Tanaman Buah di Desa Suka Damai Kecamatan Tungkal Jaya Kabupaten Musi Banyuasin - Liani Ardila; Dewi Rosanti; Trimin Kartika (Indobiosains, 2022)
AbstractResearch on the Morphological characteristics of fruit plants in Suka Damai Village, Tungkal Jaya District, Musi Banyuasin Regency, has been carried out from April 2021 to June 2021, aims to examine the types of horticultural plants through the morphological characteristics of roots, stems, leaves, flowers and fruit. This study uses a descriptive survey method by exploring the village area as many as 3 RT. Observations were made by looking directly at fruit horticultural plants and then recorded, photographed and then described the morphology. The results obtained 17 species are fruit plants. The species obtained had roots (Radix) with a fibrous root system (Radix adventicia) and a tap (Radix primaria). Stem morphology (Caulis) includes stem types, namely wet stems, grasses and woody. Leaf morphology (Folium) consists of single leaf (Folium simplex) and compound leaf (Folium compositum) with leaf structures including leaf shape (Circumscription) elongated (Oblangus), ovoid (Ovatus), lanceolate (Lanceolatus), sword (Ensiformis), triangle (Triangularis), heart (Cordatus), delta (Deltoideus), ribbon (Ligulatus), jorong (Ovalis). Flower morphology The flower morphology (Flos) is of single flower type (Planta unifloris), and compound flowers (Anthotaxis), which are found in the leaf axils (Flos axillaris) and leaf tips (Flos terminalis). The morphology of fruit (Fructus) was in the types of pseudo fruit (single pseudo, double pseudo, compound pseudo) and true fruit (buni fruit, stone fruit, box fruit, pod). Keywords: horticultural crops, plant morphology